2023
DOI: 10.3390/ijms241310522
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Stimulation Reverses Memory Impairment in Adrβ3KO Male Mice

Abstract: Norepinephrine plays an important role in modulating memory through its beta-adrenergic receptors (Adrβ: β1, β2 and β3). Here, we hypothesized that multisensory stimulation would reverse memory impairment caused by the inactivation of Adrβ3 (Adrβ3KO) with consequent inhibition of sustained glial-mediated inflammation. To test this, 21- and 86-day-old Adrβ3KO mice were exposed to an 8-week multisensory stimulation (MS) protocol that comprised gustatory and olfactory stimuli of positive and negative valence; int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…More recently, in a pro-inflammatory mouse model, multisensory stimulation reversed memory impairment (Ravache et al, 2023). Karoglu-Eravsar et al (2021) further showed that EE with sensory components prevented age-related decline in synaptic dynamics in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, in a pro-inflammatory mouse model, multisensory stimulation reversed memory impairment (Ravache et al, 2023). Karoglu-Eravsar et al (2021) further showed that EE with sensory components prevented age-related decline in synaptic dynamics in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles used animal models to investigate the effects of different interventions on memory and learning [ 20 , 21 , 22 ]. These studies explored the roles of multisensory stimulation, glucocorticoid receptor antagonism, and recognition memory in modulating hippocampal neurogenesis, synaptic plasticity, and fear-related behaviors.…”
Section: Special Issue Articlesmentioning
confidence: 99%
“…These studies explored the roles of multisensory stimulation, glucocorticoid receptor antagonism, and recognition memory in modulating hippocampal neurogenesis, synaptic plasticity, and fear-related behaviors. Ravache et al investigated the effects of multisensory stimulation on memory impairment in a mouse model of obesity [ 20 ]. The authors showed that multisensory stimulation reverses memory deficits induced by the lack of adrenergic beta-3 receptor, which is involved in thermogenesis and energy expenditure.…”
Section: Special Issue Articlesmentioning
confidence: 99%
“…Additionally, non-invasive brain stimulation techniques have become an integral aspect of clinical research in mental illnesses [13,14]. Methods such as transcranial magnetic stimulation and transcranial direct current stimulation have been employed in preclinical models to investigate their potential therapeutic alternatives [15,16]. These techniques offer a unique opportunity to modulate neural activity in specific brain regions, mimicking the neuromodulatory effects observed in human studies [17][18][19].…”
Section: Topic Articlesmentioning
confidence: 99%